5α-reductase 1 mRNA levels are positively correlated with TRAMP mouse prostate most severe lesion scores - Opoku-Acheampong, Alexander; Henningson, Jamie N.; Beck, A. P.; Lindshield, Brian L. (My University, 2017)
Background The contribution of 5α-reductase 1 and 5α-reductase 2 to prostate cancer development and progression is not clearly understood. TRAMP mice are a common prostate cancer model, in which 5α-reductase 1 and 5α-reductase 2 expression levels, along with prostate lesions scores, have not been investigated at different time points to further understand prostate carcinogenesis. Method/Principal findings To this end, 8-, 12-, 16-, and 20-week-old male C57BL/6TRAMP x FVB mice prostate most severe and most common lesion scores, 5α-reductase 1 and 5α-reductase 2 in situ hybridization expression, and Ki-67, androgen receptor, and apoptosis immunohistochemistry levels were measured. Levels of these markers were quantified in prostate epithelium, hyperplasia, and tumors sections. Mice developed low- to high-grade prostatic intraepithelial neoplasia at 8 weeks as the most severe and most common lesions, and moderate- and high-grade prostatic intraepithelial neoplasia at 12 and 16 weeks as the most severe lesion in all lobes. Moderately differentiated adenocarcinoma was observed at 20 weeks in all lobes. Poorly differentiated carcinoma was not observed in any lobe until 12-weeks-old. 5α- reductase 1 and 5α-reductase 2 were not significantly decreased in tumors compared to prostate epithelium and hyperplasia in all groups, while proliferation, apoptosis, and androgen receptor were either notably or significantly decreased in tumors compared with prostate epithelium and hyperplasia in most or all groups. Prostate 5αR1 levels were positively correlated with adjusted prostate most severe lesion scores. Conclusion Downregulation of androgen receptor and 5α-reductase 2, along with upregulation of 5α- reductase 1 in tumors may promote prostatic intraepithelial neoplasia and prostate cancer development in TRAMP mice. © 2017 Opoku-Acheampong et al.This is an open access article distributed under the terms of the Creative Commons Attribution License, which permits unrestricted use, distribution, and reproduction in any medium, provided the original author and source are credited.
Citation: Opoku-Acheampong, A. B., Henningson, J. N., Beck, A. P., & Lindshield, B. L. (2017). 5α-reductase 1 mRNA levels are positively correlated with TRAMP mouse prostate most severe lesion scores. Plos One, 12(5). doi:10.1371/journal.pone.0175874